ANALISIS KANDUNGAN MIKROPLASTIK PADA AIR, UDANG DAN SEDIMEN DI TAMBAK BUDIDAYA KABUPATEN PINRANG - Agria Budi Darmawan; Jayadi Jayadi; Andi Tamsil (JURNAL AKUAKULTUR, TEKNOLOGI DAN MANAJEMEN PERIKANAN TANGKAP, ILMU KELAUTAN, 2025)
Pallameang Village is a village located in Pinrang Regency located in Mattiro Sompe District. The waters in Pallameang Village have the potential to be polluted by microplastics due to high community activities and fishing activities. One of the fishing activities in Pallameang Village is traditional tiger prawn cultivation. This study aims to determine the amount of abundance and characteristics (color, shape, and size) of microplastics contained in water, shrimp and sediment in tiger prawn pond cultivation in Pallameang Village, Pinrang Regency. The method used is quantitative descriptive and analyzed using the Rapid Assessment Microplastic method. The results show that the average abundance of microplastics in water is 142.85 particles/L, shrimp 0.9 particles/gr, and sediment 0.21 particles/gr. The characteristics of the form of microplastics found in water and shrimp are in the form of fibers while in sediments they are in the form of fibers and fragments. The most dominant microplastic color was found in water with a percentage of 57.5% blue, shrimp with a percentage of 100% blue, and sediment with a percentage of 28.9% transparent. The size of microplastics most commonly found in water is 0.5-1.0 mm, shrimp 1.0-5.0 mm, and sediment 0.1-0.5 mm.